1989
DOI: 10.1177/002224298905300106
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of International Marketing Strategy: Some Research Hypotheses

Abstract: Two aspects of international marketing strategy standardization are process and program standardization. A framework for determining marketing program standardization is introduced. Factors affecting program standardization are examined critically. In an attempt to establish a research agenda on the standardization issue, the author develops research propositions for each factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
308
3
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(328 citation statements)
references
References 31 publications
13
308
3
4
Order By: Relevance
“…These two measures were chosen because the measurement of such similarities can be conveniently compared across industrial firms. The similarities also adhere to applications in previous studies (Douglas and Wind, 1987;Jain, 1989;Wolf and Egelhoff, 2002).The ratings were made on fivepoint Likert scales, on which scale point 1 represented 'Very different' and point 5 represented 'Very similar'.…”
Section: Methodsmentioning
confidence: 86%
“…These two measures were chosen because the measurement of such similarities can be conveniently compared across industrial firms. The similarities also adhere to applications in previous studies (Douglas and Wind, 1987;Jain, 1989;Wolf and Egelhoff, 2002).The ratings were made on fivepoint Likert scales, on which scale point 1 represented 'Very different' and point 5 represented 'Very similar'.…”
Section: Methodsmentioning
confidence: 86%
“…In the wake of the globalisation trends the last couple of decades a number of writers have examined the content of internationalisation strategy -as opposed to the process -(e.g. Craig/Douglas 2000, Hout et al 1982, Porter/Takeuchi 1986, Jain 1989, Ohmae 1989, Yip 1995, Solberg 1997, Zou/Cavusgil 1996, 2002. Different dimensions of strategy have been treated, for instance: -Standardisation/adaptation of the marketing mix -Coordination and control of operations -Centralisation/decentralisation of decisions -Market concentration/market spread -Consolidation/expansion -Sequencing of market entry -Competitive reaction -Entry/operation modes We have adopted the classification presented by Solberg (1997) and Solberg et al (2004), who identified nine different strategies.…”
Section: Strategy Development Network Access and International Commimentioning
confidence: 99%
“…In functional terms convergence encompassed both organizational change processes (e.g. global business streaming- Andrews, Chompusri and Baldwin, 2003), marketing standardization strategies (Theodosiou and Katsikeas, 2001;Jain, 1989) and human resource management practices, instanced by Western performance appraisal processes (Rowley and Benson, 2002;Entrekin and Chung, 2001).…”
Section: Post-crisis Convergence: Firm-level Implicationsmentioning
confidence: 99%